Evaluation of the competitiveness of the system of passenger transportation by railway - Žvirblis, Algis; Butkevičius, Jonas (Transport, 2004)
Considering the impact of technological factors on the system of passenger transportation, the emphasis is placed on competitiveness as a criteria of evaluation the efficiency of its performance. The system of passenger carriage by railway is analysed in terms of an automatic control system. An algorithm for constructing a formalized competitiveness model is provided defining local competitive abilities in respect to the units of a technological complex including the component of infrastructure determined by its state and the admissible speed and the component referring to rolling stocks. Thorough examination of the routes based on the methods offered in this work is needed to make proper decisions about their efficiency. A number of actions which should be taken to largely improve passenger carriage by railway is also described.First Published Online: 27 Oct 2010